Potential Zoonotic Gastrointestinal Nematode Infection from Goat in Sumedang - Nisa Fauziah; Hazel Faras Alhafiz; Naufal Fakhri Nugraha; Ita Krissanti; Muhammad Ersyad Hamda; Lia Faridah (BALABA: JURNAL LITBANG PENGENDALIAN PENYAKIT BERSUMBER BINATANG BANJARNEGARA, 2021)
Potential of zoonotic gastrointestinal nematode infection from livestock in Indonesia is still often overlooked. Farms with a risk for nematodes infection would create a risk of infecting the local community with zoonotic gastrointestinal nematodes. This study aimed to assess the risk of gastrointestinal nematodes from goats that have zoonotic potential in Cibeureum Wetan, Sumedang, and to identify the incidence of nematodes infection among goats. This was a cross-sectional study conducted in August to November 2019 with a total of 52 samples of feces collected directly from goat’s rectum to prevent soil contamination. Sampling was performed randomly from goats raised at the Agriculture and Self-Sustaining Village Training Center (Pusat Pelatihan Pertanian dan Pedesaan Swadaya, P4S) Simpay Tampomas, Sumedang, Indonesia. The GPS point of the sampling location was recorded. Samples were then examined using the concentration sedimentation method at the Parasitology Laboratory, Faculty of Medicine, Universitas Padjadjaran. Results showed that 22 of 52 samples were positive for gastrointestinal helminth eggs, contained of Bunostomum sp., Strongyloides sp., Haemmonchus sp., Trichostrongylus sp., Toxocara sp. and Trichuris sp. The nematode parasites found are parasites that often infect goats.